Urgensi Pengawasan dalam Aktivitas Dakwah - Nurqistiani Nurqistiani; Siti Maudillah; Yuniati Yuniati; M. Nabil Al-Fayidh (Pusat Riset dan Inovasi Nasional, 2025)
Controlling of da'wah activities is very important to ensure that the message conveyed is in accordance with the true teachings of Islam and does not deviate from the principles of sharia. In the era of globalization, the challenges faced in da'wah are increasingly complex. Various understandings and interpretations of Islamic teachings have emerged, which often cause conflict and division among the people. Therefore, supervision is the key to preventing ideological deviations and extremism that can damage the image and disrupt social harmony. This research was conducted using the literature study method, namely a research method that is carried out by reading and reviewing various written sources related to the topic being discussed. These sources can be books, scientific journals, articles, or other documents that are relevant to the theme of supervision in da'wah activities. Definition of Supervision Purpose of Supervision Challenges Risks of Da'wah Without Supervision (Controlling) Solutions in Resolving Various Existing Challenges Supervision of da'wah activities is crucial to maintaining religious harmony and national security. However, the challenges faced are very complex, covering regulatory, social, technological, and security aspects. Collaborative efforts are needed between the government, clerics, society, and technology to create an effective monitoring system without stifling freedom of expression. With the right approach, da'wah can remain a means of enlightenment, not a source of conflict.